2001
DOI: 10.1097/00006534-200112000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Prefabricated Thin Flap Using the Transversalis Fascia as a Carrier

Abstract: To harvest a thin flap from the groin and hypogastric area, the authors developed a new prefabricated flap using the transversalis fascia as a carrier. The transversalis fascia is a very thin and abundantly vascularized tissue nourished by the deep inferior epigastric vessels. Flap prefabrication was performed by inserting the transversalis fascia between the thinly undermined skin flap and the tissue expander placed beneath the skin flap, followed by a pretransfer delay procedure around the flap. After a 3-we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The fascial flap also provides the best thickness and vascularity for skin flap expansion. Implantation of the transversalis fascia, 26 the lateral thigh fascia 12 and the radial forearm fascia 10,[14][15][16] require microsurgical anastomosis to the tissue requiring expansion in contrast to the rotation of temporoparietal fascial flap, 11,13,15,16,21 which is simply rotated and implanted underneath the supraclavicular or neck regions. As shown in our investigation, the temporal and parietal regions were generally preserved by the primary facial injury and may be available in all patients requiring facial resurfacing.…”
Section: Discussionmentioning
confidence: 99%
“…The fascial flap also provides the best thickness and vascularity for skin flap expansion. Implantation of the transversalis fascia, 26 the lateral thigh fascia 12 and the radial forearm fascia 10,[14][15][16] require microsurgical anastomosis to the tissue requiring expansion in contrast to the rotation of temporoparietal fascial flap, 11,13,15,16,21 which is simply rotated and implanted underneath the supraclavicular or neck regions. As shown in our investigation, the temporal and parietal regions were generally preserved by the primary facial injury and may be available in all patients requiring facial resurfacing.…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, a vascular carrier does not contain any tissue other than a densely spread capillary network, and it is maintained with a very long pedicle with large-caliber blood vessels that facilitates microvascular anastomosis. Several tissues, such as muscle, 19 fascia, 11,[20][21][22] omentum, 23 and vessel bundles 13,24,25 have been used as the carriers. Kimura et al 22 reported that the vessel bundle and muscle are not adequate as carriers for making a thin and large prefabricated skin flap.…”
Section: Discussionmentioning
confidence: 99%
“…The vascularized fascia may be the most suitable tissue as a carrier for making a thin prefabricated skin flap. There have been several reports that described use of the temporoparietal fascia, 11,20 radial forearm fascia, 21 and transversalis fascia 22 for flap prefabrication.…”
Section: Discussionmentioning
confidence: 99%
“…33 These results were similar to those of Takato et al 36 and Itoh, 37 who reported that flap prefabrication can be successfully extracted at least 3 weeks after pedicle implantation. With respect to clinical applications of prefabricated flaps, Pribaz and Fine, 24 Morrison et al, 38 Safak and colleagues, 39 and other investigators, [40][41][42][43] have also shown promising clinical potentials for this type of flap.…”
Section: Discussionmentioning
confidence: 99%